Correction to: Immunotherapy Utilizing the Combination of Natural Killer– and Antibody Dependent Cellular Cytotoxicity (ADCC)–Mediating Agents with Poly (ADP-ribose) polymerase (PARP) Inhibition - Kathleen E. Fenerty; Michelle Padget; Benjamin Wolfson; Sofia R. Gameiro; Zhen Su; John H. Lee; Shahrooz Rabizadeh; Patrick Soon-Shiong; James W. Hodge (Journal for ImmunoTherapy of Cancer, 2019)
Following publication of the original article [1], an error was noted in the GAPDH in the western blot depicted in Figure 4b.